2015
DOI: 10.1111/epi.13061
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological profiles of patients with juvenile myoclonic epilepsy and their siblings: An extended study

Abstract: SUMMARYObjective: To examine executive function, intelligence, visuospatial skills, language, memory, attention, reaction time, anxiety, depression, and emotional and behavioral traits most frequently associated with executive dysfunction in patients with juvenile myoclonic epilepsy (JME) compared with a sibling and a normal control group under video-electroencephalography (video-EEG) conditions. Methods: Twenty-two sibling pairs, one with JME, were compared with 44 controls matched for age, gender, and educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 29 publications
6
50
0
2
Order By: Relevance
“…This area is associated with rational thinking process, and most notably active during the Stroop task [30]. Behavioral studies suggested that JME patients showed more errors in Stroop test [31,32], and atypical ACC was found to be partly correlated to these poor performance[33,34]. Collectively, the abnormalities of ACC reported in our study may be the potential structural explanation for these behavioral deficits.…”
Section: Discussionsupporting
confidence: 54%
“…This area is associated with rational thinking process, and most notably active during the Stroop task [30]. Behavioral studies suggested that JME patients showed more errors in Stroop test [31,32], and atypical ACC was found to be partly correlated to these poor performance[33,34]. Collectively, the abnormalities of ACC reported in our study may be the potential structural explanation for these behavioral deficits.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, it has been demonstrated that the neuropsychological deficits delineated in JME are present in otherwise healthy siblings as well. 30 Bearing in mind that frontal lobe dysfunction and risk-taking behavior may lead to psychosocial difficulties like drug abuse and criminal behavior, it is possible that such problems may be found to a greater extent in families affected by JME. 28,31 We find it remarkable that the single factor standing out as overrepresented in the self-withdrawal JME group was having a parent with psychosocial difficulties like addiction or violent behavior.…”
Section: Self-withdrawal Of Antiepileptic Drugsmentioning
confidence: 99%
“…This bidirectional relationship has been reported for a variety of comorbid conditions including depression, suicidality, ASD, ADHD, psychosis, and schizophrenia (Lin, Mula, & Hermann, 2012). Not only are there shared susceptibilities between epilepsy and specific behavioral comorbidities, but of particular interest is evidence of co-aggregation of cognitive, behavioral, and even brain structural abnormalities in the siblings and parents of persons with epilepsy compared to general population controls (Alhusaini et al, 2015; Aronu & Iloeje, 2011; Badawy, Vogrin, Lai, & Cook, 2013; Chowdhury et al, 2014; Hesdorffer, Caplan, & Berg, 2012; Iqbal et al, 2015; Iqbal et al, 2009; Singhi, Bansal, Singhi, & Pershad, 1992; Tsai et al, 2013; Verrotti et al, 2013; Wandschneider et al, 2014; Wandschneider et al, 2010). These observations suggest the presence of distinct endophenotypes underlying epilepsy and some of its comorbidities, suggesting possible shared genetic mechanisms, although the influence of environmental factors remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%